Teaching macroeconomics from Islamic perspective - Khalid, Haniza; Duasa, Jarita; Ariffin, Muhammad Irwan (2018)
The purpose is to describe the objectives, methods and underlying strategy of incorporating Islamic perspectives in three courses taught in KENMS: one from each degree, masters and PhD levels.